2022
DOI: 10.1055/s-0042-1756296
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Analysis of Breast Reconstruction with Fat Grafting Content on TikTok

Abstract: As of November 2021, TikTok has one billion monthly active users and is recognized as the most engaging social media platform. TikTok has seen a surge in users and content creators, ranging from athletes to medical professionals. In the past year, content creators have utilized the app to advocate for social reforms, education, and other uses that were not previously considered. Breast cancer is the most commonly diagnosed cancer in women, with an expected 281,550 new cases of invasive breast cancer in 2021. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The video retrieval process in existing literature involved both the user-preference-based MLS strategy [ 19 , 30 , 31 , 33 35 ] and the mainly used DCS strategy [ 13 , 16 , 36 40 ], and four cut-off sample sizes ( n = 50 [ 13 , 33 ], 100 [ 16 , 19 , 34 , 35 , 38 40 ], 150 [ 30 ] and 200 [ 31 , 36 , 37 ]) were all reported. This is the first study to analyze whether these two retrieval algorithms influence the audience-available video quality and audience engagement.…”
Section: Discussionmentioning
confidence: 99%
“…The video retrieval process in existing literature involved both the user-preference-based MLS strategy [ 19 , 30 , 31 , 33 35 ] and the mainly used DCS strategy [ 13 , 16 , 36 40 ], and four cut-off sample sizes ( n = 50 [ 13 , 33 ], 100 [ 16 , 19 , 34 , 35 , 38 40 ], 150 [ 30 ] and 200 [ 31 , 36 , 37 ]) were all reported. This is the first study to analyze whether these two retrieval algorithms influence the audience-available video quality and audience engagement.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study describing the content of the most viewed TikTok videos on the larger topic of breast cancer. Our review of the literature revealed one prior publication focusing on fat grafting in breast cancer [ 27 ]. Prior research evaluated breast cancer coverage on various social media platforms [ 16 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…3 Chen Z, Pan S, Zuo S. Anal Fissures 62 videos TikTok: An Opportunity for Antibiotic Education? 22 Evans E, Gory L, O'Kane A Antibiotics 300 videos A Cross-Sectional Analysis of Breast Reconstruction with Fat Grafting Content on TikTok. 23 Gupta R, John J, Gupta Across all health topics, the median DISCERN and PEMAT-AV scores were 2.02±0.23/5 and 56 ±16.488, respectively (95% CI; Figure 2).…”
Section: Researchmentioning
confidence: 99%